Extraction of clarithromycin and atenolol by cuttlefish bone powder. Issue 20 (18th October 2018) - Khazri, Hassen; Ghorbel-Abid, Ibtissem; Kalfat, Rafik; Trabelsi-Ayadi, Malika
ABSTRACT: Pharmaceutical products including analgesics, antibiotics, and antiepileptics are often present in wastewater treatment effluents, lakes, and rivers and have been found in waterways of many countries. The adsorption of two common pharmaceuticals present in surface waters, clarithromycin (CLR) and atenolol (ATN), onto cuttlefish bone powder treated with HCl has been investigated. Adsorption experiments were carried out at different pH conditions and the experimental equilibrium data were fitted to the Langmuir and Freundlich. For the same experimental conditions (pH = 7), the estimated adsorption capacities are from 34.5 mg g −1 for CLR and 39.5 mg g −1 for ATN. The influence of adsorption pH was established for each compound. The negative values of Δ G at different temperatures for all samples indicate the spontaneous nature of the sorption process.